Examine languagealitys effects in Fereshteha khodkoshi kardand's - Mehrdad Zarei; esmat khoeini (مطالعات زبانی و بلاغی)
Reza Barahani in the 70s proposes a new theory called "languageality". The aim of which is the freedom of language from the shackles of meaning, conventional imagery and other issues that he believes are imposed on language. Baraheni's theory attracted some attention as much that Seyyed Mehdi Mousavi tried to use some of these topics in the old form of lyric poetry. Fereshteha khodkoshi kardand is mentioned as the first collection of postmodern sonnets. In the language of this collection's sonnets, there are certain grammatical approaches that indicate his influence on Baraheni's theory of linguistics. In the present study, with a descriptive-analytical approach and by the method of poetry language library, this work has been studied in two axes of grammar and syntax. In the morphology part, the deviation that Mousavi has done under the influence of Barahani in the field of Letters and compounds has been examined and in the syntax section of the deconstructions that have taken place as a result of escape from patriarchal syntax and launcher displacements application are explained. In the end, it was found that the confusion of vocabulary and sentence syntax showed a disturbed and chaotic structure in the text of the sonnet, which, while different, lacks the necessary aesthetics and emotion.